Servant Leadership of School Administrators Under the Secondary Educational Service Area Office Bangkok 1 - Toochinda, Varisara; Silanookit, Chonmanee (Legal State Journal, 2023)
This research article aims to study and compare the servant leadership of school administrators under the Secondary Educational Service Area Office Bangkok 1classified by education level, work experience and school size. This research uses a quantitative research model. The samples used in the research 357 teachers. The instrument used to collect the data was a questionnaire. The discrimination was between 0.60 and 1.00, and the reliability was .987. The statistics used in the data analysis were frequency distribution, percentage, mean, standard deviation, t-test, One-way analysis of variance and Scheffe’s comparison test. The results showed that (1) the servant leadership of school administrators under the Secondary Educational Service Area Office Bangkok 1 overall and each side, was at a high level; (2) teachers with different educational levels had opinions towards the servant leadership of school administrators under the Secondary Educational Service Area Office Bangkok 1 overall and individual aspects are not different; and (3) teachers with different work experience and school size had different opinions on the servant leadership of school administrators under the Secondary Educational Service Area Office Bangkok 1 overall and each aspect were significantly different at the .05 level.